DNA PROTECTIVE ACTIVITY OF Artemisia spp HAIRY ROOT EXTRACTS - Duplij V.; Afanasieva K.; Chopei M.; Matvieieva N. A. (Biotechnologia Acta)
Artemisia spp. plants are known as producers of bioactive compounds and used both in folk and traditional medicine. They possess antitumor, antiproliferative, antidiabetic, antimicrobial, antiviral, antioxidant, and anti-inflammatory activity.